1999
DOI: 10.1295/polymj.31.172
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Weight Effect on Local Motion of Polystyrene Studied by the Fluorescence Depolarization Method

Abstract: ABSTRACT:The molecular weight effect on the local motion of polystyrene (PS) was examined in dilute solutions by the fluorescence depolarization method. Four PS samples with the fluorescent probe, anthryl group, in the middle of the main chain were synthesized by the living anionic polymerization. The molecular weight of samples varied from ca. 6.4 x 10 3 to 9.2 x 10 4 Solvents were benzene, a good solvent and ethyl acetate, a poor solvent. In both solvents, the relaxation time increased with the molecular wei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(40 citation statements)
references
References 28 publications
2
38
0
Order By: Relevance
“…The same analysis above also suggests that the segmental mobility of polymer chains is a possible limiting factor for crystal growth. It is known that a polymer’s segmental mobility in a dilute solution decreases with increasing molecular weight but reaches a plateaus near DP = 100 . This dependence is consistent with standard models .…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The same analysis above also suggests that the segmental mobility of polymer chains is a possible limiting factor for crystal growth. It is known that a polymer’s segmental mobility in a dilute solution decreases with increasing molecular weight but reaches a plateaus near DP = 100 . This dependence is consistent with standard models .…”
Section: Discussionsupporting
confidence: 87%
“…It is known that a polymer's segmental mobility in a dilute solution decreases with increasing molecular weight but reaches a plateaus near DP = 100. 32 This dependence is consistent with standard models. 31 This molecular weight dependence of segmental mobility is in excellent agreement with that of a polymer's effect on crystal growth (Figure 8).…”
Section: ■ Discussionmentioning
confidence: 99%
“…Figure 3 shows that the value of τ r increases slowly with decreasing temperature and then increases steeply below the transition temperature. The temperature dependence of τ r can basically be attributed to the variation in the activity of the thermal motion of the gellan chains, as was reported for nonelectrolyte polymer systems 10–14. The rotational relaxation of the fluorescent probe labeled in the polymer chain is achieved by the thermal motion of neighboring polymer segments, consisting of coupled librations and conformational transitions 22.…”
Section: Resultsmentioning
confidence: 55%
“…Therefore, if the fluorescent probe is labeled in a polymer chain, the local chain mobility can be estimated as the rotational relaxation time of the fluorescent probe 10–19. Fluorescence depolarization studies have focused on non‐electrolyte polymer systems; it has been reported that the chain mobility of nonelectrolyte polymers is determined by the steric hindrance in internal rotation and the chain entanglement 10–17. Regarding polysaccharides, amylose and dextran in dilute aqueous solutions were previously examined, and the effect of coil‐helix conformational transition on the chain mobility was discussed 15.…”
Section: Introductionmentioning
confidence: 99%
“…The relaxation time of the probe was estimated through the measurements of the decay of the fluorescence anisotropy ratio. The local motion of polymer chain has been extensively studied for the polymers with the fluorescent probe labeled in the main chain. We examined the local motion of polymer chains labeled with anthracene as the fluorescent probe in dilute solutions and discussed the effects of several molecular factors such as solvent condition, , molecular structure of polymer, molecular weight, and the position along a chain on the local chain mobility . However, there still remain some questions to be solved.…”
Section: Introductionmentioning
confidence: 99%